Reality and new dilemmas of service quality (passenger handling) in airlines industry: The case of Air Asia - Romle, Abd Rahim; Zainol, Asif Zamri; Said, Ilias (Universiti Utara Malaysia Press, 2007)
Airline services are known to be the most elaborate in terms of service.There are many breakdowns of services in airlines industry.They can be divided into four main areas; these are passenger services, baggage or cargo services, engineering services and catering services.In Malaysia, the airlines industry was monopolized by the Malaysian Airlines until 2001, when Air Asia decided to introduce no-frills discounted airfares.However, with the introduction of cheap frills discounted airline through Air Asia, the need of service quality itself is being questioned.Are the passengers more receptive towards price rather than service quality when it comes to flying domestically? The purpose of this survey is to explore the passengers' views on service quality provided by Air Asia that they had experienced.Chang and Yeh's (2002) modified model of SERVQUAL was used in this study while integrating Parasuraman et al. (1985) original five-point Likert scale. The study was conducted in the departure hall of Langkawi International Airport.The respondents consisting of 88 passengers who have had experience with this airline and were selected based on convenience sampling.Descriptive analysis and mean comparison are used to analyze the data. There were two main findings in this exploration.First, Air Asia does not meet the service quality standard expected by the passengers.Secondly, majority of the respondents participating in this study, choose price over service quality.